1998
DOI: 10.1002/(sici)1097-4679(199802)54:2<267::aid-jclp16>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Italian, Japanese and American students' responses to the Adolescent Reinforcement Survey Schedule

Abstract: The Italian form of the Adolescent Reinforcement Survey Schedule (ARSS-I) was administered to (N = 648) high school boys and girls from northern and central Italy. Their responses were factor analyzed using a principal component. VARIMAX rotation procedure (SAS Institute, Inc., 1990). The 10 interpretable factors from the Italian data were compared and contrasted to factor analytic results from Holmes (1991, 1994) studies using American and Japanese students. Additionally, the Italian data analyses includes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…First, studies should examine in more detail demographic variations in reinforcer preferences. Research with the RSS has found few age and cultural differences but many significant gender differences (Galeazzi, Franceschina, Cautela, Holmes, & Sakano, 1998;Holmes et al, 1994;Holmes, Sakano, Cautela, & Holmes, 1991). For example, males reported greater preferences for sexual activities and substance use, and females reported greater preferences for social and academic activities.…”
Section: Discussionmentioning
confidence: 99%
“…First, studies should examine in more detail demographic variations in reinforcer preferences. Research with the RSS has found few age and cultural differences but many significant gender differences (Galeazzi, Franceschina, Cautela, Holmes, & Sakano, 1998;Holmes et al, 1994;Holmes, Sakano, Cautela, & Holmes, 1991). For example, males reported greater preferences for sexual activities and substance use, and females reported greater preferences for social and academic activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some privileges are more desirable for particular youth within the residential setting. Researchers have identified some group differences in preference between genders, cultures (Italian, Japanese, and American), and ages (e.g., Galeazzi, Franceschina, Cautela, Holmes, & Sakano, 1998;Holmes et al, 2004;Pellegrini, 1992). For example, in a study examining preference for play, Pellegrini (1992) found that younger boys were more likely to prefer playing outdoors than older boys or girls.…”
mentioning
confidence: 99%